“It had to happen”: Individual memory biases and collective memory - Klein, Olivier (2010)
For the purpose of the study we varied the outcome of a sequence of ambiguous behaviors performed by an imaginary individual during World War II. Compared to a control condition where no outcome was presented, this person either ended up saving Jews (heroic behavior) or denouncing Jews to the Gestapo (cowardly behavior). After one week, behavioral antecedents that were consistent with the outcome were likely to be recalled and communicated. Results suggest a tendency  towards forming extreme impressions of the target, depending on the outcome. These extreme impressions in turn guide the recall and evaluations of predictability, and also impact on communication about these episodes and thereby on the formation of collective memory.